An eye‐catching atypical illustration of the evaluation and management of AL amyloidosis secondary to myeloma. Issue 12 (9th December 2021) - Khan, Shamis; Premji, Sarah; Huang, Quillan; Verstovsek, Gordana; Bushan, Sita; Yellapragada, Sarvari Venkata
Abstract: We present a case of a 58‐year‐old male patient who presented to his primary care clinic with complaints of eye swelling and fatigue. Workup ultimately led to a diagnosis of AL amyloidosis secondary to myeloma based on SLiM‐CRAB criteria. We discuss his diagnostic workup, treatment, and subsequent relapse. Abstract : In the setting of AL amyloidosis, relapse can occur despite initial complete resolution, and treatment is guided by patient factors, disease factors, and treatment toxicity.